2016
DOI: 10.3390/w8030095
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Acceptance of Novel Silver-Impregnated Ceramic Cubes for Drinking Water Treatment in Two Field Sites: Limpopo Province, South Africa and Dodoma Region, Tanzania

Abstract: Diarrheal disease and environmental enteropathy are serious public health concerns in low-income countries. In an effort to reduce enteric infection, researchers at the University of Virginia developed a new point-of-use (POU) water treatment technology composed of silver-impregnated porous ceramic media. The ceramic is placed in a 15 L plastic container of water in the evening and the water is ready to drink in the morning. The purpose of this study was to assess field performance and local acceptance of tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(5 reference statements)
2
11
1
Order By: Relevance
“…In addition, there was little to no detectable residual chlorine in the municipal tap water to prevent recontamination. A previous study performed in an adjacent community showed higher household treatment levels; however, this may have been due to intervention studies in that community (the community in question was excluded from this study because of previous interventions) [47]. The study also concurred that boiling was the most common method employed.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, there was little to no detectable residual chlorine in the municipal tap water to prevent recontamination. A previous study performed in an adjacent community showed higher household treatment levels; however, this may have been due to intervention studies in that community (the community in question was excluded from this study because of previous interventions) [47]. The study also concurred that boiling was the most common method employed.…”
Section: Discussionsupporting
confidence: 65%
“…Almost all mothers (n = 390, 96.5%) completed at least secondary school education and were on average 28 years old (SD: 6.7; Table 1). The mean monthly income for the household was 1920 South African Rand (ZAR) (approximately USD135 in June 2016), which is consistent with that of previous studies in the area, 24 and households had on average 2.4 children younger than 15 years (SD: 1.2). The majority of participants most frequently obtained drinking water from the municipality (piped into their yard, n = 91, 22.5%; or from a public stand pipe, n = 77, 19.1%) or from surface water through a piped system (into their yard, n = 100, 24.8%; or from a public stand pipe, n = 46, 11.4%).…”
Section: Resultssupporting
confidence: 88%
“…Both technologies have proven to be highly effective in treating water, showing up to a 3.2 log reduction in total coliform bacteria during field studies in South Africa and Tanzania. 23,24 Ceramic water filters also reduced diarrheal rates among HIV-positive individuals in Limpopo, South Africa, by 79%. 15 However, it is unknown whether the use of these technologies can translate to improvements in child health outcomes, particularly linear growth.…”
Section: Introductionmentioning
confidence: 99%
“…The results from this study suggest that this novel silver impregnated ceramic technology is effective, safe, socially acceptable, and commercially viable. Kahler et al [37] reported the economic viability of this product elsewhere. They also conducted a field study in South Africa, and examined a cost model based on a "willingness to pay" study.…”
Section: Discussionmentioning
confidence: 99%